Impact of early pericardial fluid chymase activation after cardiac surgery - Butts, Brittany; Goeddel, Lee A.; Zheng, Jingyi; Pat, Betty; Powell, Pamela; Mobley, James; Ahmad, Sarfaraz; Steele, Chad; McGiffin, David; Davies, James E.; George, James F.; Melby, Spencer J.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Chymase is a highly destructive serine protease rapidly neutralized in the circulation by protease inhibitors. Here we test whether pericardial fluid (PCF) chymase activation and other inflammatory biomarkers determine intensive care unit length of stay, and explore mechanisms of chymase delivery by extracellular vesicles to the heart. PCF was collected from adult patients (17 on-pump; 13 off-pump) 4 hours after cardiac surgery. Extracellular vesicles (EVs) containing chymase were injected into Sprague–Dawley rats to test for their ability to deliver chymase to the heart. The mean intensive care unit (ICU) stay and mean total length of stay was 2.17 ± 3.8 days and 6.41 ± 1.3 days respectively. Chymase activity and 32 inflammatory markers did not differ in on-pump vs. off-pump cardiac surgery. Society of Thoracic Surgeons Predicted Risk of Morbidity and Mortality Score (STS-PROM), 4-hour post-surgery PCF chymase activity and C-X-C motif chemokine ligand 6 (CXCL6) were all independent predictors of ICU and total hospital length of stay by univariate analysis. Mass spectrometry of baseline PCF shows the presence of serine protease inhibitors that neutralize chymase activity. The compartmentalization of chymase within and on the surface of PCF EVs was visualized by immunogold labeling and transmission electron microscopy. A chymase inhibitor prevented EV chymase activity (0.28 fmol/mg/min vs. 14.14 fmol/mg/min). Intravenous injection of PCF EVs obtained 24 hours after surgery into Sprague Dawley rats shows diffuse human chymase uptake in the heart with extensive cardiomyocyte damage 4 hours after injection. Early postoperative PCF chymase activation underscores its potential role in cardiac damage soon after on- or off-pump cardiac surgery. In addition, chymase in extracellular vesicles provides a protected delivery mechanism from neutralization by circulating serine protease inhibitors.